N‐Heterocyclic Olefins on a Metallic Surface – Adsorption, Orientation, and Electronic Influence - Felix Landwehr; Mowpriya Das; Sergio Tosoni; Juan J. Navarro; Ankita Das; Maximilian Koy; Markus Heyde; Gianfranco Pacchioni; Frank Glorius; Beatriz Roldan Cuenya (Advanced Materials Interfaces)
Abstract N‐Heterocyclic olefins (NHOs), possessing highly polarizable and remarkably electron‐rich double bonds, have been effectively utilized as exceptional anchors for surface modifications. Herein, the adsorption, orientation, and electronic properties of NHOs on a metal surface are investigated. On Cu(111), the sterically low‐demanding IMe‐NHO is compared to its analogous IMe‐NHC counterpart. High‐resolution electron energy‐loss spectroscopy (HREELS) measurements show for both molecules a flat‐lying ring adsorption configuration. While the NHC adopts a dimer configuration including a Cu adatom, the NHO chemisorbs over a C–Cu bond perpendicular to the surface. This distinct difference leads for the IMe‐NHOs to have a higher thermal stability on the surface. Moreover, IMe‐NHOs introduce a higher net electron transfer to the surface compared to the IMe‐NHCs, which results in a stronger effect on the work function. These results highlight the role of NHOs in surface science as they extend the functionalization capabilities of NHCs into stronger electronic modification.